Mirogabalin as a novel calcium channel α2δ ligand for the treatment of neuropathic pain: a review of clinical update - Yang, Fei; Wang, Yan; Zhang, Mingjie; Yu, Shengyuan (Frontiers in Pharmacology, 2024)
Neuropathic pain (NP) is often caused by diabetic neuropathy, chemotherapy, or spinal cord lesions and is associated with significant economic burden and poor quality of life. Sophisticated etiology and pathology recognized different pharmacologic interventions, and hitherto, the reported analgesic efficacy and safety of guideline-recommended drugs are not satisfactory. Overall, this article reviews the mechanism of α2δ ligand, the clinical pharmacokinetics, efficacy, safety and cost-effectiveness of mirogabalin for the treatment of NP, offering clinical perspectives into potential benefits of NP-related syndrome or comorbidities. Mirogabalin, a novel voltage-gated Ca2+ channel (VGCC) α2δ ligand with selective binding affinities to α2δ-1 than α2δ-2 subunit, exhibited a wider safety margin and a relatively lower incidence of adverse events compared with other gabapentinoids. Randomized-controlled trials and open-label studies have demonstrated the efficacy and long-term safety of mirogabalin in Asian patients with diabetic peripheral neuropathic pain (DPNP), postherpetic neuralgia (PHN), and central NP. Analgesic effects of mirogabalin for the single or add-on treatment on chemotherapy-induced peripheral neuropathy and orthopedic disease/postoperation-related NP were also evidenced. To date, mirogabalin is approved for the general indication of NP in Japan, PNP in South Korea, and DPNP in the Chinese Mainland and DPNP, PHN in Taiwan (China). In summary, mirogabalin emerges as a promising option for NP; further research is warranted to refine wider treatment strategies, flexible dosing in real-world setting.